Behavioral factors associated with medication adherence among hypertensive patients using the theoretical domains framework - Van De Tran; Thi My Loan Vo; Quang Loc Duyen Vo; Minh Trung Nguyen; Minh Cuong Nguyen; Rebecca Susan Dewey; Thi Hai Yen Nguyen (Exploratory Research in Clinical and Social Pharmacy)
Background: Theoretical exploration of the behavioral factors associated with adherence to medication in hypertensive patients has been limited in previous studies. Objectives: This study aims to understand the associations between demographic and health characteristics and behavioral factors for medication taking, and how these predict medication adherence. Methods: A cross-sectional survey was conducted in hypertensive outpatients, with a sample size of 399 participants. Behavioral factors predicting medication taking, designed to align with the theoretical domains framework, and the medication adherence scale were used. Behavioral factors were determined using principal component analysis, and their associations with demographic and health characteristics and medication adherence were analyzed using non-parametric statistics. Results: Four behavioral factors were identified: (F1) negative emotions and beliefs about capabilities, (F2) beliefs about consequences, (F3) knowledge and skills, and (F4) social support. F1 showed a strongest inverse association with medication adherence (ρ = −0.25; p < 0.01). Significantly higher F1 scores were recorded in hypertensive patients with secondary school or lower education (p < 0.001), income less than 4 million VND (p = 0.03), who were currently smoking (p = 0.018), self-reporting chest pain or discomfort (p < 0.001), and of older age (p < 0.01). Conclusions: Certain demographic and health characteristics were significantly associated with emotions and beliefs about capabilities to take medication, which, in turn, was significantly associated with medication adherence. Future research should design interventions that focus on reassuring patients of the need and of their ability to overcome their worries and sadness and reduce their difficulties in using medications.